2011
DOI: 10.1111/j.1467-7687.2011.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

Gesture in the developing brain

Abstract: Speakers convey meaning not only through words, but also through gestures. Although children are exposed to co-speech gestures from birth, we do not know how the developing brain comes to connect meaning conveyed in gesture with speech. We used functional magnetic resonance imaging (fMRI) to address this question and scanned 8- to 11-year-old children and adults listening to stories accompanied by hand movements, either meaningful co-speech gestures or meaningless self-adaptors. When listening to stories accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 124 publications
(192 reference statements)
4
59
0
Order By: Relevance
“…speech and gesture match, mismatch or complement each other). Even though these studies find left frontal and left posterior temporal cortices to be implicated in integrating gestures with speech, they vary with respect to whether they consistently find co-speech gesturerelated activation in the following regions: left IFG, bilateral posterior superior temporal sulcus (STSp) and middle temporal gyrus (MTGp) [34,[38][39][40][41][42][43][44][45][46][47][48][49]. Interestingly, these are the areas that are also involved when increased semantic processing is required during speech comprehension.…”
Section: Interactions Between Speech and Gesture Comprehensionmentioning
confidence: 99%
See 2 more Smart Citations
“…speech and gesture match, mismatch or complement each other). Even though these studies find left frontal and left posterior temporal cortices to be implicated in integrating gestures with speech, they vary with respect to whether they consistently find co-speech gesturerelated activation in the following regions: left IFG, bilateral posterior superior temporal sulcus (STSp) and middle temporal gyrus (MTGp) [34,[38][39][40][41][42][43][44][45][46][47][48][49]. Interestingly, these are the areas that are also involved when increased semantic processing is required during speech comprehension.…”
Section: Interactions Between Speech and Gesture Comprehensionmentioning
confidence: 99%
“…In the Straube et al [47] study, iconic gestures as well as grooming movements, even though used as control, activated left IFG, when compared with no movement. Dick et al [39] also found left IFG to be sensitive to meaning modulation by iconic gestures; that is, more activation in this area for complementary (speech: 'I worked all night'; gesture: type) than redundant gestures accompanying speech (speech: 'I typed all night'; gesture: type). Complementary gestures add information and require more semantic processing than redundant gestures.…”
Section: Interactions Between Speech and Gesture Comprehensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous works have investigated various aspects of the production, perception, processing, and development of gestures (e.g., Kelly & Church 1998;Kelly & Barr 1999;Mayberry & Nicoladis 2000;McNeil et al 2000;O'Neill et al 2002;Holler & Beattie 2003a;b;Holle & Gunter 2007;Özyürek et al 2007;Alibali et al 2009;Gullberg 2009;Kelly et al 2009;Kidd & Holler 2009;Botting et al 2010;Göksun et al 2010;Cartmill et al 2012;Dick et al 2012;Lücking et al 2012;Özçalişkan & Dimitrova 2013;Emmorey & Özyürek 2014;Hrabic et al 2014;Özyürek 2014;Wagner et al 2014). While many of these existing studies have examined the meanings that co-speech gestures contribute, they do not target the precise ways in which gestures may interact with the logical structure of the sentences with which they co-occur.…”
Section: Experimental Investigationmentioning
confidence: 99%
“…Effective connectivity analysis was performed with SEM using the AMOS software. We followed the standard procedure to study neural systems connectivity modeling (61), recently implemented in fMRI (that provides comparable neural signals to those measured with fNIRS) (62)(63)(64). This approach included the following steps (described in detail in SI Materials and Methods): specification of the Fig.…”
Section: Methodsmentioning
confidence: 99%